Geographical features of formation of the reclamation system of the Bahna Valley - Hodzinska, Iryna (Yuriy Fedkovych Chernivtsi National University, Ruta, 2021)
Intensive economic development of landscape complexes throughout the history of society has led to their almost complete change. In the 60-70s of the twentieth century appeared a new constructive direction in geography, which combined theoretical and practical nowledge. As a result, it has become possible to identify changes in natural landscapes caused by human economic activity and to ationally use and protect natural resources.
Культурний ландшафт як географічний феномен Матеріали Міжнародної наукової конференції (23–25 вересня, 2021)
Keywords: Bahna Valley